Comportamento do hidrociclone filtrante frente às modificações no diâmetro de underflow e no tubo de vortex finder - Almeida, Celso Augusto Koboldt (2008)
Filtering hydrocyclones are similar equipaments to the conventional hydrocyclone except by the fact they have filtering conical region. In this way, during the operation of this equipament, besides the feed streams, the underflow and the overflow, observed commonly, the porous conical region produces liquid by the filtration process. The filtration in the conical region of the hydrocyclone is able to reduce the Euler number and increase the particulate material collection efficiency in this type of centrifugal separator, verified by the experimental results, despite the low filtered rate. In this context, VIEIRA (2006) obtained a hydrocyclone with optimal geometry, denominated HF11, using techniques of CFD validated by experimental data. This optimal filtering hydrocyclone allowed to obtain results with low Euler numbers and high collection efficiencies. In order to give continuity to the studies mentioned previously, this work is aimed at examining the influence of the vortex finder length and the underflow diameter about the solid-liquid separation process in the filtering hydrocyclone HF11 and in the conventional hydrocyclone similar HC11. Through the techniques of factorial planning, of the experimental results and of the computational fluidodynamic, was possible analyze the influence of the vortex finder and of the underflow diameter about the solid-liquid separation. From the previous analysis, was verified that the Euler number and the cut diameter were inversely proportional to the variations of the underflow diameter. On the other hand, the Euler number was straightly proportional to the modifications of the vortex finder. About the influence of the vortex finder length on the cut diameter, also it was observed that intermediate values of this geometrical variable provided the biggest particulate material collection efficiencies. Therefore, the ideal combination between the underflow diameter and the vortex finder length in a filtering hydrocyclone will depend of the technical-operational interests of each user. Considering the experimental interval utilized in this work, if the priority of the user is to know the classification by particle size, a underflow diameter and a vortex finder length of 5 and 21 mm, respectively, would be the appropriatest. However, if the objective is only to concentrate the underflow current in solids, would be appropriate a underflow diameter and a vortex finder length of 3 and 12 mm, respectively.